ANALISIS SIFAT FISIKA DAN KIMIA TANAH DI DESA BALESARI KECAMATAN NGAJUM KABUPATEN MALANG - Hadi Pratiwi, Anggraeni; Abidin, Zainal; Faroni, Fariq; Asyrofi, Muhammad (RADIKULA: Jurnal Ilmu Pertanian, 2022)
Balesari is one of the areas located in Ngajum, Malang. The farmers in this area have several agricultural coomodities such as ginger, vegetables, and coffee. One of the main conditions for obtaining optimal production in the cultivation of agricultural crops is fertile soil conditions. This study was conducted in Balesari, Ngajum, Malang. This study aimed to determine the physical and chemical properties of the soil in Balesari, Ngajum, Malang. The results indicated that the soil in the research location has a sandy silt loam texture. The chemical properties of the soil have varied propersties with the actual soil pH ranging from 5.42-5.70 with the criteria being slightly acidic and acidic, C-organic ranged from 1.8827 to 2.2653% with low and medium criteria, total N ranged from 0.1392 to 0.2294% with low and moderate criteria, total P ranged from 0.0704 to 0.423% with low criteria, total K ranged from 0.105 – 0.900% with low and high criteria, and the cation exchange capacity (CEC) ranged from 39.2109 – 41.9049 me.100gr-1 with high and very high criteria.